From Contestation to Affirmation. Warmian Bishop Philipp Krementz in the face of the Dogma of Papal Infallibility - Żmudziński, Marek Andrzej (Studia Warmińskie, 2024)
The proclamation of the dogma of papal infallibility has raised many questions and doubts in the Church. Already during the preparations and deliberations, a number of bishops were asking that the conditions of this infallibility be abandoned or at least defined in accordance with doctrinal and historical tradition. In essence, the idea was to anchor the teaching authority and competence of the pope in the infallibility of the entire Church and the college of bishops. Bishop Philipp Krementz was among those clearly opposed to the new dogmatic formula. However, after the dogma was promulgated and a moderate interpretation developed, he accepted the new truth and became its defender. The article describes this breakthrough on the theological, episcopal and diocesan levels. In doing so, it reveals the figure of the Warmian bishop as an informed transmitter of the faith, a loyal member of the episcopal college and a responsible shepherd of the local Church.